Greco-Roman cities at the crossroads of cultures : the 20th anniversary of Polish-Egyptian conservation mission Marina El-Alamein - Bakowska-Czerner, Grazyna; Czerner, Rafał (Archaeopress archaeology., 2019)
These papers present research from different regions ranging from ancient Mauritania, through Africa, Egypt, Cyprus, Palestine, Syria, as well as sites in Crimea and Georgia. Topics include: topography, architecture, interiors and décor, religious syncretism, the importance of ancient texts, pottery studies and conservation.